Literature Riview : Masalah Terkait Malnutrisi: Penyebab, Akibat, dan Penanggulangannya - LAILANI, FADIA KALMA; Yuliana, Yuliana; Yulastri, Asmar (JGK: Jurnal Gizi dan Kesehatan, 2022)
Background: Malnutrition Is a state of a person's status who is malnourished, or whose nutrition is below average. Malnutrition is a deficiency of nutrients such as proteins, carbohydrates, fats and vitamins needed by the body. 1 How to assess nutritional status can be done with anthropometric, clinical, biochemical, and biophysical measurements. . Children who are malnourished will experience a decrease in their immune system so that children are susceptible to infectious diseases. Pathophysiologically, malnutrition and malnutrition in children under five (12-59 months) experience protein energy deficiency, iron nutritional anemia, disorders due to iodine deficiency (GAKY) and vitamin A deficiency. Deficiency of the four sources above in children under five can inhibit growth, reduce immune system so that they are susceptible to infectious diseases, resulting in low levels of intelligence, decreased physical abilities, impaired physical and mental growth, stunting, blindness and death in children. Purpose: to gain a better understanding of problems related to malnutrition in terms of causes, effects, and remedies. Method: In this study we used a research method in the form of library research, which is a series of studies relating to library data collection methods, or the research was collected through various kinds of library information (scientific journals, books, encyclopedias, magazines, newspapers, and documents). Conclusion: Based on the research results obtained from reviewing journals that match the theme, it can be concluded that nutritional status in children under five is often used to see the nutritional status of society in general.